KAJIAN KRITIK SANAD DAN MATAN HADIS TENTANG WANITA YANG HARAM DINIKAHI - ., Kamarudin (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
In this article, we want to emphasize one of the hadiths of the Prophet Muhammad regarding women who are forbidden to marry. There are many cases among Muslims who marry women without thinking about their religion and lineage and do not consider the hadith of the Prophet saw so that the author wants to examine the hadith about women who are forbidden to marry. By using the Takhrij Hadith Method which uses the Book of Mu'jam al Mufahraz by Wensinck and Tahzibul Kamal fi Asma Al-Rijal by al-Mizzi, the author will review the validity of the hadith, so that the Islamic community knows the quality of the hadith. After conducting this research, it can be concluded that the hadith about women who are forbidden to marry are Sohih, so there needs to be confirmation from scholars or religious leaders that this hadith is worthy of being used as a reference for Muslims in choosing the woman to marry.